Effects of Low-Level Laser Therapy in a Black Patient Victim of Facial Burn: A Case Report - Vidal, Iago Barbosa; Silva, Patrícia Teixeira; Rocha, Igor Santos da; Dantas, Tales Freitas; Silveira, Marcelo Leite Machado da; Carneiro, Bárbara Gressy Duarte Souza; Jorge, Maria Joceleide; Gondim, Ricardo Franklin; Menezes Junior, José Maria Sampaio; Bezerra, Ariel Valente (Brazilian Journal of Case Reports, 2024)
Burns are injuries resulting from exposure to thermal, chemical, or electrical sources, ranging from small blisters to deep lesions affecting the skin, subcutaneous tissues, tendons, muscles, and bones. Although Low-Level Laser Therapy (LLLT) is widely recognized in the literature as an adjunctive treatment for burns, its application in Black patients remains limited. This case report describes the treatment of a Black patient with facial burns using LLLT with infrared laser (4 Joules per point) and red laser (1 Joule per point), both at a power of 100mW. The results indicated that LLLT is promising, reducing the length of hospital stay, minimizing infections, and improving quality of life, while also providing analgesia, comfort, and accelerating healing. The technique also contributed to aesthetic and functional rehabilitation, enhancing the patient’s self-esteem. However, due to the scarcity of studies in the literature regarding this therapy in Black patients, there is a pressing need for irradiation protocols supported by robust clinical trials, including significant samples that consider the severity of burns, skin color, age, and location of the injuries.